Identifikasi Nematoda Usus dan Cestoda Usus pada Feses Anak Sekolah Dasar di Desa Bekoso Kalimantan Timur - Firda Zalianty; Dian Nurmansyah; Puspawati Puspawati; Lala Foresta Valentine Gunasari (Lembaga Pengembangan Kinerja Dosen, 2026)
Helminth infections caused by Soil Transmitted Helminths (STH) and Taenia sp. remain a major public health concern in tropical regions, including Indonesia, particularly among elementary school children. This study aimed to identify the presence of eggs and larvae of intestinal nematodes and cestodes in fecal samples collected from elementary school children in Bekoso Village, East Kalimantan. The research employed a descriptive survey method with a cross-sectional approach, and laboratory examinations were conducted using the Kato-Katz technique. A total of 16 fecal samples were examined to detect Ascaris lumbricoides, hookworm, and Taenia sp. eggs. The results showed that 12.5% of samples were positive for hookworm eggs, 12.5% for Taenia sp. eggs, and 6.25% for Ascaris lumbricoides eggs. These findings indicate that poor personal hygiene and inadequate environmental sanitation contribute to an increased risk of intestinal helminth transmission. The study highlights the importance of preventive efforts through the promotion of clean and healthy living behaviors, consistent use of footwear, handwashing with soap, and community participation in mass deworming programs to reduce the prevalence of intestinal helminth infections among elementary school children.